Analysing from experience : Gustav Mahler's Quartetsatz for piano and strings - Du Plessis, Jacques (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 2015)
Musical analysis has traditionally been located within the context of musicology. It is therefore an activity usually considered the purview of music scholars rather than practical musicians. The musical analyses produced by music scholars therefore provide us with intellectual understandings of musical works, rather than insights into the experience of listening to or playing music. In this thesis, I will propose that those agents involved in practical music-making can produce insights into musical works that are as valid as the work of traditional music scholarship. I will attempt to re-conceptualize the position of the 'knower' or 'experiencer' - the performer - of music as one with primary access to knowledge of a musical work, and therefore ideally suited to offer analyses of these works. The establishment of the performer as a bearer of central analytical knowledge functions in direct opposition to the traditional distinction between 'theory' and 'practice'. My thesis will trace the Platonic origins of the philosophical separation of practice and research, and as an alternative to the traditional separation of practice and research, I shall explore the concept of Practice-Based Research (PBR). My exploration of PBR will be informed by phenomenological approaches to music scholarship. As a field of enquiry which concerns itself with experience, the phenomenology of music suggests that the mind and body of the practitioner are important sources of musical insight. To address this issue, Bourdieu's notion of habitus will be explored. The habitus will be shown to contain a vast network of socio-cultural codes informing the practitioner's relationship with the musical work. A central aim of this thesis is to explore the possibilities of using practice-based research as the foundation for the study and analysis of a composition, in order to allow for a deeper understanding of the work by means of the generation and harnessing of practical knowledge. Thus, the theoretical outline of PBR provided in this thesis will be applied to a piece of practical performance-based analysis. As such, an analysis of Mahler's Quartetsatz will be used as the basis on which to draw knowledge in this project.
Keywords: Mahler, Gustav, 1860-1911. -- Quartet, piano, violin, viola, cello, A minor; Musical analysis; Music appreciation; Phenomenology and music